CULTIVAR PREFERENCE PATTERN AND AMYLOLYTIC ENZYME ACTIVITY OF MANGO MEALY BUG (Drosicha mangiferae G.) FED ON DIFFERENT HOST PLANT CULTIVARS - NANDI, PARTHA SARATHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
To elucidate whether there is a cultivar preference of mango mealy bug, (Drosicha mangiferae G.), the number of them were counted in 30 cm branch of panicle randomly from four different directions in Fazli, Guti, Lakhanbhog, Gopalbhog and Langra cultivars at orchards of Kaligram and Chanchal of Malda.Similarly number of mango mealy bug present in 10 cm2 area of main trunk in those five cultivars were also noted. Oviposition preference, growth and weight gain pattern of mango mealy bug were also studied by feeding third instar nymphs of them with leaves of those different cultivars for two weeks. The number in the field and growth parameters of laboratory reared mango mealy bug have established the cultivar preference of mango as Fazli> Guti> Lakhanbhog> Gopal Bhog> Langra. The effect of food quality of different cultivars on the amylolytic enzyme activity was also carried out by measuring starch amount of different cultivars, quantifying protein and performing alpha-amylase assay of mango mealy bug fed on those cultivars. Starch amount differed significantly in different cultivars. Fazli had highest amount of starch followed by Guti, Lakhanbhog, Gopalbhog and Langra. Availability of lesser starch in Langra or Gopalbhog caused down regulation of alpha-amylase in these less preferred cultivars. So, alpha-amylase and protein amount enzyme activity of mango mealy bug was found to be low in mealy bugs fed in Langra (0.017 U/ml ± 0.007) and Gopalbhog (0.019 U/ ml ± 0.0007) cultivars compared to highly preferred Fazli or moderately preferred Guti and Lakhanbhog. Fazli reared pest showed highest (0.047 U/ml ± 0.003) amylolytic activity followed by Guti (0.44 U/ml ± 0.0005) and Lakhanbhog (0.038 U/ml ± 0.001). This current study is very much helpful to choose the suitable cultivar for propagation. Moreover, the effect of nutrient on digestive physiology of insect can also be understood.